Legal Consequences of Violating Arbitration Agreement and Arbitrator Appointment Agreement under Indonesian Obligation Law Principles - Nugrahenti, Meydora Cahya; Hernawan, Ari (Kosmik Hukum, 2025)
Subsequent to Law Number 30 Year 1999 on Arbitration and Alternative Dispute Resolution (AADR LAW), violations of arbitration agreements and arbitrator appointment agreements still persist in Indonesia. Parties bound by arbitration agreements have initiated court proceedings, while losing parties have sought to nullify arbitral awards on grounds not stipulated in Article 70 of the AADR LAW. Given the apparent ease of such actions without legal repercussions, this article examines the legal consequences of violating these agreements based on obligation law principles. This research uses a normative juridical approach, utilizing secondary data on arbitration, agreement law, and obligation law, including legislation, scholarly literature, and journal articles. This article finds that arbitration agreements and arbitrator appointment agreements constitute obligations from contractual arrangements. Both agreements fulfill the four elements of obligation: legal relationship, property, parties, and performance. Legally, a breach of these agreements constitutes a default, which may result in legal action against the defaulting party. The AADR Law does not comprehensively regulate this matter. Consequently, this article advocates for developing legal frameworks through additional regulations concerning default parameters in both agreements, along with their legal consequences in rights claims. This approach aligns with commutative justice principles, ensures contractual justice, and facilitates parties' adherence to arbitration and arbitrator appointment agreements.